Resources and cognitive-affective-motivational characteristics of Philippine-and US-based Filipino Mathematics teacher a framework for professional development - Arceo, Virginia R. (College of Education, University of the Philippines Diliman, 2020)
In light of the recent implementation of the curriculum, along with efforts by the government and private institutions to uplift the Philippine education system, this research sought to compare mathematics teacher competence in the country to their counterparts in the United States of America. This comparison of two groups of mathematics teachers focused on the identification of significant differences in cognitive abilities and affective-motivational characteristics as inspired by Blomeke and Delaney (2012). Mathematics Content Knowledge (MCK) and Mathematics Pedagogical Content Knowledge (MPCK) constituted cognitive abilities, while affective-motivational characteristics included intrinsic motivation, self-regulation, and professional beliefs. Furthermore, this study investigated other factors or resources that contributed to teacher characteristics. This mixed methods study utilized comparative explanatory sequential design. Quantitative data was first gathered with researcher developed and expert-validated instruments, and adapted questionnaires. Qualitative data was collected in the form of interviews in order to support and explain the quantitative results. Significant differences in the cognitive domain of reasoning between the two groups of Filipino mathematics teachers were found in favor of the US group using the Mann-Whitney U Test. There were also significant differences in their professional beliefs, where the Philippine-based respondents believed that learning is more teacher-centered while their counterparts saw mathematics learning more student-centered. Using PLS-SEM, it was found that intrinsic motivation and professional beliefs had a significant negative influence on MCK which implies that the teachers perceived intrinsic motivation and beliefs can also be detrimental when it causes them to lower the amount of effort they give towards enriching their MCK. It was found that location has a significant negative moderating effect on the influence of self-regulation to MCK. The influence of self-regulation of US-based mathematics teachers on their MCK was lower than the influence of self-regulation of the MCK of Philippine-based respondents because the former cannot foreseeably set goals or self-evaluate themselves with regard to topics not in their mathematics education programs. Moreover, using Spearman Correlation analysis, teacher resources such as use of technology, teaching materials, teaching assignment, and frequency of teacher trainings had small to moderate correlation to cognitive abilities and affective-motivational characteristics. These investigations informed the creation of a professional development framework to guide teachers, administrators, and professional development program developers in designing holistic trainings that could equip Filipino mathematics teachers with enhanced competencies for increased effectiveness and global competitiveness. Application of the proposed professional development framework was recommended in order to test its effectiveness and accuracy in enhancing teacher competence.